Covalent Linkage of BODIPY‐Photosensitizers to Anderson‐Type Polyoxometalates Using CLICK Chemistry. Issue 68 (29th September 2021) - Cetindere, Seda; Clausing, Simon T.; Anjass, Montaha; Luo, Yusen; Kupfer, Stephan; Dietzek, Benjamin; Streb, Carsten
Abstract: The covalent attachment of molecular photosensitizers (PS) to polyoxometalates (POMs) opens new pathways to PS‐POM dyads for light‐driven charge‐transfer and charge‐storage. Here, we report a synthetic route for the covalent linkage of BODIPY‐dyes to Anderson‐type polyoxomolybdates by using CLICK chemistry (i. e. copper‐catalyzed azide‐alkyne cycloaddition, CuAAC). Photophysical properties of the dyad were investigated by combined experimental and theoretical methods and highlight the role of both sub‐components for the charge‐separation properties. The study demonstrates how CLICK chemistry can be used for the versatile linkage of organic functional units to molecular metal oxide clusters. Abstract : Covalent functionalization o f Anderson‐polyoxometalates with BODIPY light‐absorbers using CLICK chemistry is reported. The resulting photosensitizer‐polyoxometalate dyads are characterized by photophysical and theoretical methods, highlighting the electronic interactions between the sub‐components, and their possible application in visible light‐driven chemistry.